PROPUESTA DE UN CONTROL SUPERVISOR PARA REGULAR LA TENSIÓN DE SALIDA DE UN CONVERTIDOR BOOST UTILIZANDO LA ENTROPÍA APROXIMADA COMO DETECTOR DE EVENTOS - José Mendoza; Eliezer Colina; Edgar Chacón; Wilfredo Rodríguez (European Scientific Journal, ESJ, 2014)
This work is mainly aimed to design a supervisory control system for regulating, very precisely, the output voltage for a boost converter, based on the model of a hybrid plant. The theory of sliding mode control is used to synthesize a controller for the continuous dynamics. Now, to solve both the problem of discontinuity as the problem of insensitivity to uncertainty in the load resistance of such converter had to design a hybrid output feedback controller to guarantee the output voltage to a desired value. Particularly an approximate entropy (ApEn) concept is used as an innovative method that could detect any event generated on the continuous time dynamics in the hybrid system. It was found that the hybrid plant supervisor provides good results in terms of robustness to disturbances, maintaining a good dynamic response.